Optimization of Mixed Fermentation Conditions of Dietary Fiber from Soybean Residue and the Effect on Structure, Properties and Potential Biological Activity of Dietary Fiber from Soybean Residue - Xifei Xu; Xuejing Zhang; Mubai Sun; Da Li; Mei Hua; Xinyu Miao; Ying Su; Yanping Chi; Jinghui Wang; Honghong Niu (Molecules, 2023)
Soybean residue is a by-product of soybean product production that is wasted unreasonably at present. Accomplishing the efficient utilization of soybean residue can save resources. A composite microbial system was constructed using lactic acid bacteria (LAB) and Saccharomyces cerevisiae (SC), and modified soybean residue was prepared by solid fermentation. In order to explore the value of modified soybean residue as a food raw material, its physical and chemical properties, adsorption properties, and antioxidant properties were studied. The results showed that the soluble dietary fiber (SDF) yield of mixed fermentation (MF) increased significantly. Both groups of soybean residues had representative polysaccharide infrared absorption peaks, and MF showed a looser structure and lower crystallinity. In terms of the adsorption capacity index, MF also has a higher adsorption capacity for water molecules, oil molecules, and cholesterol molecules. In addition, the in vitro antioxidant capacity of MF was also significantly higher than that of unfermented soybean residue (UF). In conclusion, our study shows that mixed fermentation could increase SDF content and improve the functional properties of soybean residue. Modified soybean residue prepared by mixed fermentation is the ideal food raw material.